Studies in cost analysis - Solomons, David (Homewood, Ill. : R. D. Irwin, 1968)
This book brings together some of the best work done in the field of industrial accounting. The collection is primarily intended for students of accounting and business administration.
First ed. published in 1952 under title: Studies in costing.
Includes bibliographical references and index
ahz 03/04/2019
Loans
Keywords: Cost accounting